Application of latent class analysis to estimate susceptibility to adverse health outcomes based on several risk factors - Dey, Ankita; Chakraborty, Arun K.; Majumdar, Kunal K.; Mandal, Asok K. (International Journal Of Community Medicine And Public Health, 2016)
Background: The study demonstrates the use of latent class analysis (LCA) to segregate population in two latent classes e.g. susceptible or not susceptible to adverse health outcomes according to the observed risk factors as a method of medical diagnosis. Methods: The present study uses a secondary data set on 420 patients referred to the University of California, Los Angeles (UCLA). Adult Cardiac Imaging and Hemodynamics Laboratories for Dobutamine stress echocardiography (DSE) between March1991 & March1996. LCA is used for estimating the individual item-response probabilities in each latent group and also the latent class sizes. The observed variables or indicators of the latent subgroups are the common risk factors viz. history of smoking, history of cardiac issues etc. The interaction effect of hypertension & diabetes is also included in the analysis. Results: Based on the behaviour of the estimates of latent class model parameters, the unobserved groups are identified and named. Proportion of individuals falling in each latent class are approximately 0.20 & 0.80 respectively. The susceptibility to adverse health outcomes in future is the most in male individuals having a positive history of hypertension and/or diabetes, as the corresponding indicators have higher positive item-response probabilities (0.72 & 0.83 respectively) than the rest. Conclusions: The study briefly explains the application of LCA for identifying subgroups according to susceptibility to adverse health effects in a large population. Assessment of common risk factors in predicting latent class sizes provides estimates of probabilities for being a member in each class. The importance of the combined effect of hypertension & diabetes in predicting future health problems related to cardiac issues is highlighted. Class assignments of individuals according to their pattern of response are also listed.